Same-Sex Marriage in Japan. Issue 2 (14th March 2016) - Tamagawa, Masami
ABSTRACT: Despite its apparent gay friendliness, Japanese society has witnessed few public debates or social movements in support of same-sex marriage. It seems that Japanese scholars and activists are only just beginning to advocate the legal protection of homosexual couples. Although Japan has witnessed a few recent developments toward same-sex marriage, an anti-same sex marriage perspective seems to dominate, even among Japanese scholars and activists who are gay and lesbian themselves.In order to understand Japans slow progress toward same-sex marriage, this article examines the legality of same-sex marriage in Japan, Japans apparent lack of the political and historical progress of same-sex marriage in the West, and Japanese societal and cultural features including gay adoption, invisibility and heterosexism at work and in academia. This article also compares the current debates on the legal protection of same-sex couples in Japan and Japanese feminist criticism of the Japanese family, to explain the prevalence of the anti-same sex marriage position. Further, with the notion of familial homophobia by Shulman (2009), the traditional Japanese family is defined as the grounds for homophobia. Lastly, the possibility of legalizing same-sex marriage in Japan is discussed.